Loss framing effect on reducing excessive red and processed meat consumption: Evidence from Italy. (May 2023) - Caso, Gerarda; Rizzo, Giuseppina; Migliore, Giuseppina; Vecchio, Riccardo
ABSTRACT: A reduction of meat consumption is crucial for addressing public health problems, especially in industrialized countries. Among low-cost interventions, emotionally provocative health-information strategies could be effective options in fostering meat reduction. Through an online experimental survey, administrated to a quota-based national sample ( N = 1142), this study analysed the profile of Italians consuming red/processed meat above World Health Organization (WHO) recommended amounts. Via a between-subjects design, the research tested whether two health frame-nudges (societal impact and individual impact of over consumption) persuaded these individuals to reduce future meat consumption. Results showed that adhering to an omnivore diet, higher consumption of meat than peers, household size (larger) and positive moral perception of meat consumption increased the likelihood of overconsumption. In addition, both nudges proved to be effective in positively impacting future intentions to reduce meat consumption among individuals exceeding WHO recommended amounts. The two frame-nudges were more effective among females, respondents with children in the household and individuals with a low health status perception. Highlights: A between-subjects design tested two loss-frame nudges on Italian meat consumers. Individual framing reduced future intentions of red/processed meat consumption. Societal framing reduced future intentions of red/processed meat consumption. Both loss-frames impacted individuals with a non-positive perceived health status.